Statistical optimization with nonlinear constraints and parameter identification for the cutoff height of pressure ridges - Tan, B.; Wang, Xiangyu; Wang, L.; Peng, L.; Li, Z. (2016)
Sociedade Brasileira de Matemática Aplicada e Computacional.To determinate the cutoff height of pressure ridges on the sea ice surface, a statistical optimal model with nonlinear constraints is established. The performance criterion consists of two parts: the deviation between the numerical results and the measured data of the ridge height; the deviation between the numerical results and the measured data of the ridge spacing. The cutoff height is taken as the identified parameter. Then, properties of the statistical optimal model and the existence of the optimal parameter are discussed, and the optimal cutoff height is identified via an optimal algorithm. Finally, the obtained optimal cutoff height is applied to separate pressure ridges from other sea ice surface undulations in northwestern Weddell Sea of Antarctic, and the correlation between the ridge height and frequency is demonstrated. Numerical results show that our model and method are both effective than the previous works.